2023
DOI: 10.1177/15353702221147566
|View full text |Cite
|
Sign up to set email alerts
|

Tastin promotes non-small-cell lung cancer progression through the ErbB4, PI3K/AKT, and ERK1/2 pathways

Abstract: Tastin might be involved in tumorigenesis, but its role in non-small-cell lung cancer (NSCLC) has not been adequately explored. This work aimed to examine tastin’s role in NSCLC and to explore the underlying mechanism. The Gene Expression Omnibus (GEO), Gene Expression Database of Normal and Tumor tissues (GENT), and Cancer Genome Atlas (TCGA) databases were used. Four GEO datasets (GSE81089, GSE40419, GSE74706, and GSE19188) containing gene expression data for NSCLC and normal tissue samples were analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To investigate the underlying reasons, a PLC GWAS conducted by James et al in 2017 demonstrated significant genomic differences between LUAD and LUSC, despite both belonging to NSCLC, suggesting potential distinct mechanisms for the development of LUAD and LUSC [ 13 ]. Furthermore, multiple previous studies have indicated the presence of shared signaling pathways, such as the PI3K pathway [ 40 , 41 ], FGFR1 pathway [ 42 , 43 ] between LUSC and CRC, implying potential common genetic origins and developmental processes between these two cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the underlying reasons, a PLC GWAS conducted by James et al in 2017 demonstrated significant genomic differences between LUAD and LUSC, despite both belonging to NSCLC, suggesting potential distinct mechanisms for the development of LUAD and LUSC [ 13 ]. Furthermore, multiple previous studies have indicated the presence of shared signaling pathways, such as the PI3K pathway [ 40 , 41 ], FGFR1 pathway [ 42 , 43 ] between LUSC and CRC, implying potential common genetic origins and developmental processes between these two cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…While it was found to be pro-tumorigenic and associated with poor prognosis in most cancer types, including glioma, lung, breast, ovarian, colorectal, gastric and prostate cancer ( Li K. et al, 2019 ; Jin et al, 2020 ; Zhao et al, 2021 ; Liu H. et al, 2022 ; Li et al, 2022 ; Wang et al, 2023 ; Yue et al, 2023 ), some studies suggest that high expression of TROAP could predict better survival in acute myeloid leukemia ( He et al, 2023 ). The tumor-promoting role of TROAP has been experimentally validated in several preclinical cancer models, including breast, kidney, liver, and prostate cancer ( Li K. et al, 2019 ; Jin et al, 2020 ; Li L. et al, 2021 ; Wang et al, 2023 ; Yue et al, 2023 ). Mechanistically, the depletion of TROAP was found to cause cell cycle arrest and inhibition of multiple cancer growth-promoting pathways.…”
Section: Understanding the Function And Regulation Of Dyrk1a Through ...mentioning
confidence: 99%
“…The experimental procedure was performed as previously described in the previous study. 32 The total protein concentrations of the cells and tissues were measured using the BCA protein quantification method (Beyotime, China). Equal amounts of protein were resolved by electrophoresis on a 10% sodium dodecyl-sulfate (SDS) gel and then transferred onto nitrocellulose membranes.…”
Section: Western Blottingmentioning
confidence: 99%